The Impact of Social Media and Key Opinion Leader on the Purchasing Behaviour in the Food and Beverage Industry in Malaysia - Ng, Wei Chien; Ong, Yong Wang; Oan, Kien Boon; Ooi, Cheah Ting; Ooi, Joanne; Habibie, Muhammad Fadhlan; Choudhary, Tanu; Raghav, Utkarsh; Kee, Daisy Mui Hung (AIBPM Publisher, 2023)
In order to survive in the food and beverage (F&B) industry in this modern era, one of the most strategic ways is to expose the brand through social media and Key Opinion Leaders (KOLs). This research paper aims to investigate the impact of social media and KOLs on purchasing behaviour in the Malaysian food and beverage industry. The quantitative research method was applied and a survey questionnaire via Google Forms was distributed to samples consist of 120 consumers in Malaysia. The findings showed that social media and KOLs significantly affect the consumers' purchasing behaviour in Malaysia's F&B industry. However, KOLs are more influential than social media in stimulating purchasing behaviour in the F&B industry among Malaysian. Accordingly, F&B businesses is strongly suggested to develop their brand existences in social media, including creating engaging and informative content, responding promptly to customer feedback, and building a loyal following of brand advocates. By leveraging social media analytics, businesses in the food and beverage industry can gain more insights related to customer behaviour and preferences to enhance their marketing strategies and product offerings.